Spatial changes of forests in a coastal and a remote mountainous area of Greece over a 65-year period - Stavros KOLIOS; George NTOGAS; Efthimios ZERVAS (European Journal of Geography)
The scope of the study is to detect spatial changes in the forested areas over six decades (1945 - 2010) of two completely different landscapes in Greece (pilot areas). The first pilot area is Kastoria which is a relatively remote and mountainous area located north-western on the Greek peninsula, while the second one is Propontida which is a coastal area in the Chalkidiki peninsula (central Macedonia, Greece). High resolution orthorectified aerial images are used to detect the general types (classes) of land use/land cover (LULC) in these pilot areas. The results reveal that during the examined period, a notable spatial growth and thickening of the forest areas was found (10,51%) in the pilot area of Kastoria. The spatial homogeneity of the forested areas in Kastoria decreased only by 2,11%. Regarding Propontida, the forested areas decreased in total about 13,02% while the agricultural and arable land has increased by 12,10%.